ОБ АНТРОПОХОРНОЙ ФАУНЕ ГУБОНОГИХ МНОГОНОЖЕК (CHILOPODA) СРЕДНЕЙ АЗИИ - Дьячков , Ю.В. (Actual problems and prospects of the study of the fauna, 2024)
The anthropochore centipede fauna of Middle Asia consists of at least six species from four genera (Geophilus Leach, 1814, Schendyla Bergsøe & Meinert, 1866, Lamyctes Meinert, 1868, and Lithobius Leach, 1814), four families (Geophilidae, Schendylidae, Henicopidae, and Lithobiidae), and two orders (Geophilomorpha and Lithobiomorpha).